PENGARUH MODEL CONTEXTUAL TEACHING AND LEARNING TERHADAP MINAT BELAJAR SISWA PENDIDIKAN AGAMA ISLAM KELAS X DI SMA MUHAMMADIYAH 1 MEDAN - Daffa Tsaqif Aufa; Makmur Syukri; Mahariah Mahariah (Jurnal Ilmiah Multidisiplin Ilmu, 2026)
This study entitled "The Effect of Contextual Teaching and Learning Model on the Learning Interest of Class X Islamic Religious Education Students at SMA Muhammadiyah 1 Medan" aims to: 1) determine the learning interest using conventional learning models in Islamic Religious Education subjects. 2) determine the learning interest of students using contextual teaching and learning models in Islamic Religious Education subjects. 3) determine the effect of using contextual teaching and learning models on students' learning interests. This study obtained the following results: 1) after the learning process was carried out in class X-2 as a control class using conventional methods, the average post-test score was 72.27. 2) after the learning process was carried out in class X-1 as an experimental class using contextual teaching and learning models, the average post-test score was 82.5. 3) The significant influence in the use of contextual teaching and learning methods in this study can be proven through the results of the independent sample test on the post-test in two groups obtained a t-value of 2.685 with a t-table value obtained from 0.05/2 = 0.025 with a df value = 44 so that a t-table of 2.0154 was found, so that H0 was rejected and Ha was accepted, it can be said that there is an influence on the use of the contextual teaching and learning model on the learning interest of class X students at SMA Muhammadiyah 1 Medan in the 2024/2025 academic year.